(3QhVI GdYdeGA aj GdJUha hGdabgs - (3MSjf Hf jMji GdHNGQj GdRfOhSJj GdMfaj, CHh Ydjs ((3eMeO Hf Ydi Hf eMeO s)
(3ChdgG (B:s
(3CeG HYO aEfj bO cfJ UfaJ gPG GdcJGH hCedjJg eQGQkG Ydi GdCUMGH hUfaJ cJGHj gPG hLeYJ aj Chd cd HGH s
(3BNQgG (B:s
(3hYf GfS QVj Gddg Yfg bGd UMHJ GdfHj Udi Gddg Ydjg hSde fja YTQI SfI MVQkG hSQkG Je GdcJGH HMeO Gddg s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B928s
(3eUOQ GbJfGA GdCUd (B:s
(3eOQSI jMjj HGTG GdLdjdj (B- (3GdehUd (B(41) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs